Perancangan Buku Fotografi Wisata Kawasan Kajoetangan Heritage - Rizky Bagus Wicaksono; Chaulina Alfianti Oktavia; Ahmad Zakiy Ramadhan (LPPM STIKI Malang, 2023)
Abstract The town of Malang has a new face that attracts the attention of local and non-local tourists, as the government of the city is poorly built but beautiful in the Kayutangan area. Kajoetangan Heritage has shortcomings, including the absence of building information, tourist spot photos, and tourist location maps, so that tourists will be confused about the tourist spot in memory of the widely spread tourism spot. Therefore, there is a need for a media that can address these shortcomings. It is media information that can provide information about the condition of the building as well as a map of the tourist area so that tourists can explore the area more thoroughly. To obtain the results of the research, the authors used qualitative methods described descriptively. The use of the method is aimed at processing or analyzing the data collected from the results of interviews with several sources. Next, define the design concept and carry out the planning process until the end of the design. Then this plan produced a photographic book entitled